ANALISIS PELAKSANAAN PROGRAM KHUSUS BINA DIRI TOILET TRAINING BAGI ANAK TUNAGRAHITA DI SLB C DIAN GRAHITA JAKARTA - B.Koba, Gracia Paskahlista; Mulia, Dedi; Maslahah, Sayidatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the limitations of the intellectual functions of children with mental retardation, which affect their adaptive abilities, particularly in self-care skills such as toilet training. Toilet training is a basic skill that plays an important role in supporting children's independence in daily life, thus requiring a special program that is planned and tailored to the individual characteristics and needs of the child. This study aims to describe the implementation of a special self-care toilet training program at SLB C Dian Grahita Jakarta, covering objectives, planning, implementation, and evaluation, as well as identifying obstacles and efforts made. The research uses a qualitative approach with a descriptive method. The informants of the study consisted of three class teachers, namely for grades II, III, and V. Data collection techniques were conducted through observation, interviews, and documentation, then analyzed through stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the program was implemented through planning based on an initial assessment tailored to the child's abilities. Implementation involved hands-on practice, the use of concrete materials, and providing positive reinforcement. Evaluation was conducted daily to monitor the child's progress. Challenges included tantrum behaviors, limited support, and lack of continuity in practice at home. Efforts made included adjusting strategies, teacher collaboration, and communication with parents.